2020
DOI: 10.9734/arrb/2020/v35i1230312
|View full text |Cite
|
Sign up to set email alerts
|

Endo-Parasites of Apparently Healthy Wild Birds in Kaduna State, Nigeria

Abstract: Aims: Wildbirds interaction with poultry increases the likelihood of exchange of parasites between wild birds and poultry highlighting the need to understand wild bird endoparasites to reduce cross-infection at the wild bird-poultry interface. This study investigates the prevalence and diversity of endoparasites among wild birds in Kaduna State to provide baseline data on the wild birds' endoparasites which could be a source of infection to poultry. Study Design: Wild birds in live wild bird markets, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The present study demonstrated a high preponderance of two species of migratory birds, namely pigeons and the African fire finches, on the selected poultry farms within Kaduna North LGA. The poultry industry is threatened by outbreaks of infectious diseases which may spread through interaction of wild or migratory birds with poultry as reported in this study (Assam et al, 2020;Bello et al, 2022). In a related study, Bello et al (2022) (Ombugadu et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
“…The present study demonstrated a high preponderance of two species of migratory birds, namely pigeons and the African fire finches, on the selected poultry farms within Kaduna North LGA. The poultry industry is threatened by outbreaks of infectious diseases which may spread through interaction of wild or migratory birds with poultry as reported in this study (Assam et al, 2020;Bello et al, 2022). In a related study, Bello et al (2022) (Ombugadu et al, 2019).…”
Section: Discussionmentioning
confidence: 56%